(untitled) (Kinesiology, 2023)
The aim of this study was to assess the effectiveness of two resistance training (RT) programmes (free weight [FW] and elastic band [EB]) on velocity variables (handball throwing velocity [HTV] and maximal theoretical velocity [V0]) using load-velocity (L-V) relationship modelling. Both programmes lasted 6 weeks and consisted of performing bench press and overarm dumbbell pull-over using free weights (FW group) or elastic bands (EB group). Nineteen male sports science students were randomly assigned to EB (n=10) or FW group (n=9). Both RT programmes increased HTV and V0, although the increment was greater in the FW (>2 m·s-1) compared to the EB group (<1 m·s-1). RT programmes had selective effects on the strength variables being FW more effective in increasing 1-repetition maximum, while EB in increasing maximal isometric force. Very large correlations were observed between two-point (L-V relationship modelled through two pairs of L and V data) and multiple-point methods (L-V relationship modelled through six pairs of L and V data) (V0: r=0.96; HTV: r=0.93). All coefficients of variation showed high validity both for V0 and HTV (≤6.2%). Altogether, FW training should be used for increasing the velocity of the throwing performance, while the two-point method for following training-induced changes. Key words: load-velocity relationship, resistance training, two-point method